2006
DOI: 10.1002/pssa.200521027
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Si and Ge quantum structures by laser‐induced etching

Abstract: Quantum structures were fabricated by immersing a crystalline silicon (Si) or germanium (Ge) wafer in hydrofluoric acid followed by laser‐induced etching with a laser photon energy of 2.41 eV. Atomic force microscopy (AFM) investigations of Si(100) etched samples reveal a complex surface morphology with pits from the top view and pillar‐like structures from the three‐dimensional view of the pit wall. For Ge(111) laser‐etched samples, AFM shows parallel wall‐type structures and Ge quantum structures on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…253,255,256 In particular, Kumar et al 251 have shown that, depending upon the laser power density, different etching stages can form cracks, pores, and pillar-like structures on the Si wafer. To get the porous structures, the laser power density should neither be very low nor very high.…”
Section: Structure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…253,255,256 In particular, Kumar et al 251 have shown that, depending upon the laser power density, different etching stages can form cracks, pores, and pillar-like structures on the Si wafer. To get the porous structures, the laser power density should neither be very low nor very high.…”
Section: Structure Characterizationmentioning
confidence: 99%
“…Typical PL spectra of PSi prepared by laser induced etching by Shin et al 253 are shown in Figure 23.…”
Section: Pl Characterizationmentioning
confidence: 99%
“…A summary of PS formation by photoetching is presented in Tables 1 and 2 (Xu and Adachi Adachi and Kubota 2007;Tomioka et al 2007;Andersen et al 1995;Noguchi and Suemune 1993;Zhang et al 1993;Cheah and Choy 1994;Jones et al 1996;Kolasinski et al 2000;Takai 2000, 2001;Mavi et al 2001Mavi et al , 2006Marotti et al 2003;Cho et al 2006;Xu and Adachi 2008;Matsui and Adachi 2012;Zheng et al 2005;Adachi and Tomioka 2005).…”
Section: Ps Layers Formed By Photoetchingmentioning
confidence: 99%
“…Analysis of the PSi layer morphology has shown that the structure of the porous layer during laser-induced etching can be controlled by the excitation laser power density, etching time, concentration of etchant, and wavelength of laser source used (Wellner et al 2000;Rasheed et al 2001;Mavi et al 2006). In particular, Kumar et al (2008) have shown that depending on the laser power density, different etching stages naming cracks, pores, and pillar-like structures can be formed on the Si wafer.…”
Section: Structure Characterizationmentioning
confidence: 99%
“…We need to note that the feature mentioned above (of PSi layer formed by laserinduced etching) may be considered a disadvantage of the discussed method of Si porosification. Typical PL spectra of PSi prepared by laser-induced etching by Mavi et al (2006) are shown in Figure 10.16.…”
Section: Movable Vesselmentioning
confidence: 99%